(untitled) (Fiep Bulletin - online, 2016)
This research investigated the insertion of history in the curriculum of undergraduate courses in Physical Education. The premise that guided this study is the idea (VIGOTISKI, 1988) that a historical study, one of the last development phase is used for an investigation of the current phenomenon. The problem did answer about what is the characterization of history as a field of scientific knowledge within the curriculum of undergraduate courses in Physical Education. The research objective was to identify the menus, curriculum subjects, teaching projects and the establishment of staff of the Higher Education Institutions (HEIs) the assumptions characterizing the mode of development of history, contemplated in the proposal for teacher education. This is a descriptive research through documentary and bibliographic analysis. Our analysis was based on documents obtained from a training institution of physical education teachers in the city of Goiânia GO / BR. There was a historian in the absence of formative development and treatment of the fragmented content to be historicized process. Considerations: a) the course ceases to gain quality in the overall training of the individual in that it points to a more specific area of training and at the expense of a more fruitful interdisciplinary practice with history; b) Given the professional profile of the IES intends to form and the possibilities of integration of history in Physical Education course that the legislation itself allows, there is a ’gap’ to be explored especially in view of the critical human development; c) Resizing the view of Physical Education in relation to history may represent a step forward in consolidating Physical Education as an area of systematized knowledge precisely the appreciation of culture for humanity developed socially.